Prediction of molecular separation of polar-apolar mixtures on heterogeneous metal-organic frameworks: HKUST-1 - Van Assche, Tom R C; Duerinck, Tim; Van der Perre, Stijn; Baron, Gino V; Denayer, Joeri F M (Langmuir, 2014)
Due to the combination of metal ions and organic linkers and the presence of different types of cages and channels, metal-organic frameworks often possess a large structural and chemical heterogeneity, complicating their adsorption behavior, especially for polar-apolar adsorbate mixtures. By allocating isotherms to individual subunits in the structure, the ideal adsorbed solution theory (IAST) can be adjusted to cope with this heterogeneity. The binary adsorption of methanol and n-hexane on HKUST-1 is analyzed using this segregated IAST (SIAST) approach and offers a significant improvement over the standard IAST model predictions. It identifies the various HKUST-1 cages to have a pronounced polar or apolar adsorptive behavior.